Tele-audiology and the optimization of hearing health care delivery - Saunders, Elaine, 1954- (IGI Global, 2019)
"This book explores the ways in which tele-audiology can be used to address the different levels of patient care, and how it can increase access, outcomes and reduce an individual's costs while also providing considerable savings to healthcare systems"--Provided by publisher.